Medicine Availability and Prescribing Policy for Non-Communicable Diseases in the Western Balkan Countries - Pekez-Pavlisko, Tanja; Racic, Maja; Kusmuk, Srebrenka (Frontiers in Public Health, 2017)
Background: During the transition processes, the Western Balkan countries were affected by conflicts and transition related changes. Life expectancy in these countries is lower, while the mortality from non-communicable diseases is higher in comparison with western and northern parts of Europe. The primary aim of this study was to analyze the treatment possibilities for the most common non-communicable diseases in the Western Balkan countries. The secondary aim was to understand and compare the policies regarding prescribing-related competencies of family physicians. Methods: In June and July 2017, a document analysis was performed of national .positive medicines lists, strategic documents and clinical guidelines for the treatment of the most frequent non-communicable diseases; arterial hypertension, diabetes, hyperlipidemia, asthma and chronic obstructive pulmonary disease. All text phrases that referred to medicines prescribing were extracted and sorted into following domains: medicine availability, prescribing policy and medication prescribing - related competencies. Results: Possibilities for treatment of arterial hypertension, diabetes, hyperlipidemia, asthma and chronic obstructive pulmonary disease vary across the Western Balkan countries. This variance is reflected in the number of registered medicines, a number of parallels and number of different combinations, as well as restrictions placed on family physicians in prescribing insulin, inhaled corticosteroids, statins and angiotensin II receptor blockers (ARBs), without consultant’s recommendation. Conclusions: Western Balkan countries are capable of providing essential medicines for the treatment of NCDs, with full or partial reimbursement. There are some exceptions, related to statins, the new generation of oral antidiabetic agents and some of the antihypertensive combinations. Prescribing-related competencies of family physicians are limited. However, this practice is not compliant with the practices of family medicine, its principles, and primary care structures, and may potentially result in increased healthcare financial ramifications to both the system and patients due to frequent referrals to the specialists.